Cyberbullying teacher's awareness, concerns, strategies, and prevention program development - Garcia, Katrina R.; Vinluan, Lorelei R.; Maligalig, Jon Paul F.; Javiniar, Joel C.; Salubayba, Teodora M. (Quezon City College of Education, University of the Philippines Diliman, 2024)
This study examined the awareness, concerns, and strategies of public high school teachers on cyberbullying prevention. A concurrent nested mixed method research design was used to explore the experiences of 52 public junior and senior high school teachers who were actively involved in cyberbullying prevention program in their respective schools. Using a three-part questionnaire, data collection covered quantitative and qualitative aspects. Thematic analysis was applied to qualitative data while quantitative data underwent frequency distribution and weighted mean calculations. The quantitative data served as the primary focus supplemented by qualitative insights to construct a comprehensive view of teachers’ experiences and perspectives on cyberbullying prevention, and these serve as bases for a guidance program. The findings reveal significant concerns of teachers regarding cyberbullying. These include insufficient supervision over students’ use of social media platforms, lack of training programs for teachers, and the absence of comprehensive school-wide cyberbullying prevention program. It is recommended that public high schools develop and implement clear and comprehensive policies and protocols, invest in professional development for teachers and other Education stakeholders, integrate cyberbullying education into the curriculum, encourage parental involvement and collaboration, establish an anti-bullying core group, prioritize counseling and mental health support, and regularly evaluate and update the cyberbullying prevention program in schools. This study provides valuable insights for the guidance profession in developing and implementing effective cyberbullying prevention programs in schools.
Thesis
Includes bibliographical references (72-79 leaves)
Keywords: Cyberbullying; Cyberbullying -- Prevention; Counseling in secondary education -- Philippines; High school teachers -- Philippines; Public schools -- Philippines